Cryo-scanning transmission electron tomography of biological cells. (7th July 2016) - Elbaum, Michael; Wolf, Sharon G.; Houben, Lothar
Abstract: Abstract : The electron microscope has made paramount contributions to understanding the structure of biological molecules, cells, and tissues. In general, the most faithful preservation of biological specimens and other soft-organic materials is achieved through cryogenic fixation. The embedding medium is the native aqueous environment itself, immobilized in vitrified form by rapid or pressurized cooling. Until recently, imaging of such vitrified thin specimens by electron cryo-microscopy has been nearly synonymous with wide-field transmission electron microscopy (TEM). Several new approaches have entered the cryo-microscopy field, including soft x-ray imaging, serial surface imaging using focused ion beam scanning electron microscopy, phase plates, and scanning TEM (STEM). In this article, we focus on the STEM method and its adaptation to biological cryo-microscopy. Cryogenic imaging of unstained specimens by STEM introduces specific challenges. Difficulties were long considered insurmountable, and the potential advantages were underappreciated. Future developments in experimental setup and detector technologies will allow for extension of the method to thicker specimens with improved resolution and analytic capabilities.